Effect of Solid Surface Vitriﬁ cation on Viability and Morphology of Canine Cumulus-Oocyte Complex - Srirungruang, Chonticha; Pongchairerk, Urai; Sirinarumitr, Kaitkanoke; Chantakru, Sirirak (Agriculture and Natural Resources, 2012)
The effects of a solid surface vitriﬁ cation (SSV) method were determined on the viability and morphology of canine cumulus-oocyte complexes (COCs). All COCs from each dog were randomly divided into ﬁ ve groups. Every group except the control (group 1) was equilibrated and separately introduced into a different recipe for the vitriﬁ cation medium. A vitriﬁ cation medium consisting of tissue culture medium (TCM) 199, supplemented with 0.5 M trehalose, 1.5 M ethylene glycol and 20% fetal bovine serum was used for COCs for groups 2 and 4, whereas a vitriﬁ cation medium consisting of TCM 199, supplemented with 0.5 M trehalose, 3 M ethylene glycol and 20% fetal bovine serum was used for groups 3 and 5. Only the COCs from groups 4 and 5 were vitriﬁ ed with the solid surface method. The survival rates of non-vitriﬁ ed and vitriﬁ ed COCs were not signiﬁ cantly different. Morphological alterations including shrinkage, disrupted oolemma, cumulus cell damage and cytoplasmic vacuolization were common features found in treatment groups. The percentages of COCs with each type of damage were not different. However, cumulus cells appeared to be the structure most affected by the SSV method.